Radiolytic Degradation of Reactive Orange-16: Degradation Pathways and Kinetics - Fifi Nurfiana; Rochmadi, Rochmadi; Rochim Bakti Cahyono; Hendig Winarno; Jonas Kristanto; Sugili Putra; Waringin M. Yusmaman; Dori Fitria; Dewi Agustiningsih (ASEAN Journal of Chemical Engineering, 2025)
Removal of Reactive Orange-16 (RO-16) dye, an emerging water pollutant and potential carcinogen, was investigated using gamma radiation. The radiolytic degradation process was studied in a batch reactor with a gamma-ray dose rate of 2426 Gy/h. Degradation of 96% RO-16 dye was achieved at 3.0 kGy irradiation dose (0.1 mM initial dye concentration). Twelve degradation products were predicted based on the m/z results from liquid chromatography-high resolution mass spectrometry (LC-HRMS). Among these, acetic acid and formic acid were identified. Possible degradation pathways were predicted based on the observed degradation products. The concentrations of the reactants RO-16, acetic acid, and formic acid were quantified to determine a specific kinetic model. The initial breakdown of the molecule occurred slowly, as indicated by the small k value, due to the steric hindrance of the large RO-16 molecule. As the molecule became smaller, the k value increased, indicating that the molecular breakdown process became faster, ultimately leading to the formation of end products. The formation of smaller molecular mass degradation products indicated that the gamma irradiation process is a promising alternative for the potential degradation of RO-16 dye.